Beirut/The Other side of the City: The Impact of Visual Texture Production of the Lebanese Postmemory Generation, 1989 - Present - Gameel Ebada, Mohamed Moustafa (AUC Knowledge Fountain, 2021)
In 1989, after the Ta'if agreement, the war in Lebanon started to fade, which ended years of one of the most destructive civil conflicts in the region with no decisive winner or loser. The year also marked the birth of a new Lebanese generation who did not experience the war in person. It is a generation of postmemory, a term Maria Hirsch coined to describe the reminisces of those who did not have a personal encounter with past traumatic events. However, it was not before February 2005, when Rafic Al-Hariri's violent assassination occurred, when the postmemory generation started to question the past. In his comprehensive study, War and Memory in Lebanon, Craig Larkin was the first to trace those who wanted to remember from the Lebanese postmemory and explore their techniques of dealing with the past. Larkin delineates the postmemory age within those who were born and live in Lebanon after 1990. Following Larkin's steps, this study explores the influence of visual and performing arts on artists’ memory of the postmemory generation and the impact and dynamics of their production. In Lebanon, the postmemory generation encounters unempathetic remembering conditions. In addition to family biases, the absence of official school history books and sects’ and political elites’ manipulation of history make it hard to know about the past. Consequently, what the young Lebanese might cognize is a "history of history of history." This study contextualizes the Lebanese postmemory’s environment by investigating two arms of Lebanese politics: the Lebanese account of the inside-outside political dynamics and Lebanon's history of the written versus oral political culture. Arguably, they provide more details than confessionalism, and their echoes on today's society is substantial. What art could achieve in such circumstances is an appealing investigation. Is it affecting the young Lebanese artists' memories or imaginations of the war? How? Based on data collected from in-depth interviews with both memory and postmemory generations, with an analysis of films, plays, and other forms of media, this dissertation attempts to understand the Lebanese artists of postmemory, and it surveys two aspects. First, the elements that mostly appear in films, plays, and other forms of visual arts that evoke their curiosity to imagine or talk about the war in their production. Second, the fundamentals that cause the postmemory confusion, which is a puzzlement that they indicated during the interviews and reflected on through their perception of the Lebanese identity.